2022
DOI: 10.1039/d2ra03051a
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the Bauschinger effect and enhancement of tension–compression asymmetry in single crystal aluminum by temperature

Abstract: The molecular dynamics method was used to study the effect of temperature on the tension–compression asymmetry and Bauschinger effect of nano single crystal aluminum (NSCA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It has been shown that the Bauschinger effect increases with decreasing grain size and depends on the degree of nonequilibrium of the grain boundaries. In a recent paper [19], a study of the temperature dependence of the Bauschinger effect in the range of 300-600 K was carried out by molecular dynamics in a nano-single crystal aluminum. It has been shown that the Bauschinger effect weakens significantly with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the Bauschinger effect increases with decreasing grain size and depends on the degree of nonequilibrium of the grain boundaries. In a recent paper [19], a study of the temperature dependence of the Bauschinger effect in the range of 300-600 K was carried out by molecular dynamics in a nano-single crystal aluminum. It has been shown that the Bauschinger effect weakens significantly with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%